Pharmaceutical Promotion in Bangladesh: Assessing the Strength of Regulatory Documents - Johora, Fatema; Rahman, Md Sayedur (Bangladesh Journal of Bioethics, 2018)
Pharmaceutical promotion is a negative influencing force for prescribing. However, very few regulatory initiatives are taken to overcome this unwarranted influence. The present research was conducted in such context with an attempt to review the regulatory documents related to pharmaceutical promotion in Bangladesh including Code of Pharmaceutical Marketing Practices (CPMP), and to compare CPMP with different global guidelines. The studied guidelines demonstrate effort to regulate promotion, though that varies to a great extent, particularly in enforcement aspects. Clearly defined ethical and legal prohibitions, provisions of punishment for violations and entrusted agency with defined authority are crucial.